Study of a complex fluid-structure dam-breaking benchmark problem using a multi-phase SPH method with APR. (July 2019) - Sun, P.N.; Le Touzé, D.; Zhang, A.-M.
Abstract: The present work is dedicated to an accurate modeling of violent Fluid-Structure-Interaction (FSI) problems using a coupled Lagrangian particle method combining a multi-phase δ -SPH scheme and a Total-Lagrangian-Particle (TLP) method. Advanced numerical techniques, e.g. Adaptive-Particle-Refinement (APR), have been included in the particle method for improving the local accuracy and the overall numerical efficiency. On one hand, this paper aims to demonstrate the capability of the proposed numerical method in modeling FSI flows with large density-ratios, strong fluid impacts, complex interfacial evolutions and considerable wall-boundary movements and deformations; On the other hand, the numerical results presented in this paper show the importance of considering the existence of air-phase in some complex FSI problems. The entrapped air-bubble, after the free-surface rolling and closing, plays an important role in the overall flow evolution and hence the hydrodynamic load on the structure. Although a density ratio as large as 1000 has been adopted, clear and sharp multi-phase interfaces, which undergo violent breakups and reconnections, are present in the numerical results, and more importantly, stable and smooth pressure fields are obtained. This contributes to an accurate prediction of the structural response, as validated by both the experimental data and other numerical results.